Teacher Competence in Designing Personalized Learning: A Systematic Literature Review - Lufita Lusiana; Rugaiyah Rugaiyah; Siti Zulaikha; Kamaludin Kamaludin (FKIP - Universitas Riau, 2026)
This study aims to identify and analyze teacher competencies in designing personalized learning in the digital era. Using the Systematic Literature Review (SLR) method based on the PRISMA model, this research reviewed 35 scientific articles published between 2020 and 2025 related to teacher competence, pedagogical design, and personalized learning. Content analysis revealed four major dimensions of teacher competence: pedagogical competence, technological competence, assessment and reflective competence, and socio-emotional and innovative competence. The findings indicate that effective personalized learning requires the integration of understanding students’ learning profiles, the use of adaptive and AI-based technologies, formative and reflective assessment practices, and the creation of empathetic and inclusive learning environments. The study implies that educational management plays a strategic role in developing continuous professional development policies to strengthen teachers’ digital literacy, reflective capacity, and pedagogical innovation. It is recommended that teacher training programs and performance management systems be optimized to support the effective implementation of personalized learning in schools.